Increased activity of frontal and limbic regions to emotional stimuli in children at-risk for anxiety disorders. Issue 1 (30th July 2015) - Christensen, Rhandi; Van Ameringen, Michael; Hall, Geoffrey
Abstract: Neuroimaging studies of children with anxiety disorders are limited, and no study has examined children who are at increased risk for developing anxiety disorders based on parental anxiety. The objective of this study was to examine the function of frontal and limbic brain regions using functional magnetic resonance imaging (fMRI) in children at risk for anxiety disorders. Study participants included high-risk children ( n =20) who had at least one parent with a primary diagnosis of social anxiety disorder and normal-risk control children ( n =19). Using fMRI, we measured the blood oxygenation level dependent response while high-risk and normal-risk children were exposed to different emotional facial stimuli. We found greater activation of frontal, temporal and limbic regions in high-risk children relative to normal-risk children during the presentation of emotional stimuli (angry and happy). These regions included the prefrontal cortex, anterior cingulate, hippocampus and insula. Our within-group analysis revealed similar patterns of hyperactivity in high-risk children with and without current anxiety symptoms. To our knowledge, this is the first study to demonstrate functional alterations in emotion-processing brain regions in children who are at risk for anxiety disorders based on parental anxiety. These findings are consistent with previous fMRI studies of pediatric anxiety and behaviorally inhibited children, and they contribute to our understanding of the neural correlates of risk for anxiety disorders. Highlights: Functional magnetic resonance imaging (fMRI) was applied in 20 children at risk for anxiety disorders. High-risk and normal-risk children were exposed to different emotional facial stimuli during fMRI. Greater activation of frontal, temporal and limbic regions was found in high-risk children than in normal-risk children during the presentation of emotional stimuli (angry and happy). Findings are consistent with previous fMRI studies of pediatric anxiety and behaviorally inhibited children, and contribute to understanding of the neural correlates of risk for anxiety disorders.